2018
DOI: 10.1007/s13197-018-3082-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel colorimetric sensor based on alginate beads for monitoring rainbow trout spoilage

Abstract: Alginate is a non-toxic, renewable, and linear copolymer obtained from the brown algae that can be easily shaped into beads. Its good gel forming properties have made it useful for entrapping food and pharmaceutical ingredients. In this study, alginate beads were used in a novel application as a colorimetric sensor in food intelligent packaging. Colorimetric sensor was developed through entrapping red cabbage extract as a pH indicator in alginate beads. The pH indicator beads were used in rainbow trout packagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 37 publications
1
26
0
1
Order By: Relevance
“…Because of irreversible spoilage and decline of quality, more attention has been provided regarding evaluation and detection of fish quality as well as revealing the mechanism of fish degradation. [7][8][9] Earlier studies confirmed that quality decline related to oxidation-reduction, enzymatic hydrolysis, microbial action. [10,11] Osmosis plays a significant role in preserving meat quality.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Because of irreversible spoilage and decline of quality, more attention has been provided regarding evaluation and detection of fish quality as well as revealing the mechanism of fish degradation. [7][8][9] Earlier studies confirmed that quality decline related to oxidation-reduction, enzymatic hydrolysis, microbial action. [10,11] Osmosis plays a significant role in preserving meat quality.…”
Section: Introductionmentioning
confidence: 92%
“…Modified sensory evaluation was carried out for odor, flavor, and texture by the sensory panel of 25 panelists. [7,9,30] Panelists provided scores on a 5-point scale: 5, excellent; 4, good; 3, acceptable; 2, fair; and 1, unacceptable. The sensory evaluation was performed in a sensory assessing room at 25°C.…”
Section: Sensory Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many fruits, berries, vegetables and flowers with colors covering practically the entire visible spectrum are dyed by natural compounds such as anthocyanins and curcumin known as natural pH indicators (Yoshida et al, 2009;Silva-Pereira et al, 2015;Choi et al, 2017;Dudnyk et al, 2018;Majdinasab et al, 2018;Saliu and Pergola, 2018;Zhai et al, 2018;Kurek et al, 2019). Upon protonation/deprotonation of these molecules, their delocalized electronic structure rearranges and the change of the total number of resonant electrons as well as their confinement result in a change of their color (Figure 4).…”
Section: Bio-based Sensorsmentioning
confidence: 99%
“…Although colorimetric pH-sensitive sensors are typically not convenient for selective analysis, it is often sufficient to evaluate the food quality based on the change of the pH, as deteriorating proteins produce alkaline volatile nitrogen compounds (cadaverine, putrescine, histamine, and ammonia) (Bulushi et al, 2009;Prester, 2011). Exploiting this indirect sensing mechanism, curcumin based indicator films, e.g., in gelatin (Musso et al, 2017) and bacterial cellulose membranes (Kuswandi et al, 2012), blueberry and red grape skin pomace in chitosan and carboxymethyl cellulose matrix (Kurek et al, 2019), chitosan-corn starch film with red cabbage extract (Silva-Pereira et al, 2015), alginate beads with red cabbage extract (Majdinasab et al, 2018) as well as red cabbage extract in pectin films (Dudnyk et al, 2018) have been shown as feasible indicators of meat, shrimp and fish spoilage by detecting amines and cyclic N-containing compounds. In a similar way, acidic CO 2 evolves during the metabolism of pathogens in the food thus lowering pH, which may be detected, e.g., by anthocyanin/polylysine in cellulose matrix in a reversible manner as demonstrated by Saliu and Pergola (2018).…”
Section: Bio-based Sensorsmentioning
confidence: 99%